SA Heart Newsletter Summer 2015 - Authors, Various (SA Heart Journal, 2017)
The 2015 SA Heart National Council held its fi rst day-long face to face meeting, during which matters that concern us all were debated in an effort to fi nally deliver effective patient care. The names and contact details of the SA Heart Exco, SIGs and Regional Branches are published in this issue for your convenience, so that you know where to raise your concerns, and offer solutions, to the problems you face. The structure, function and vision of the Association was again debated at length, and some of the important issues which were discussed will be highlighted in this newsletter.